Verbal Violence in Elementary Schools in Medan City: Sociolinguistic Study - Desy Agustina Silalahi; Mhd Pujiono; Gustianingsih Gustianingsih (BIRCU, 2023)
The purpose of this study was to identify (1) forms of verbal violence in the form of bullying in schools (2) factors that influence the occurrence of verbal violence in the form of bullying in schools and (3) the impact of verbal violence in the form of bullying in schools on social interaction environment. This type of research is a qualitative research with a descriptive design. This study uses several methods, namely the provision of data in the form of observation, interviews, and recording. The data used in the study were in the form of utterances from research subjects about verbal violence in elementary schools. The analytical method used is by means of data reduction, data presentation and drawing conclusions. The findings in this study are forms of verbal violence, namely in the form of words, phrases, clauses. There are 4 influencing factors, namely experience, environment, knowledge and economy. The impact is divided into 2, namely the negative impact, namely quiet behavior, loners, disturbances in controlling emotions such as crying, complaining and fighting. While the positive impact is a change in behavior for the better, even though it is only temporary and an aggressive attitude against.